Prototipe Penekan Tombol Otomatis Simulator Meter kWh Untuk Pengisian Token Berbasis Mikroprosesor dan API Telegram - Firmansyah, Vera; Oktaviyana, Karlina; Fathan, H. Syauqi; Muslim, Azis; Firmansyah, Firmansyah; Gunawan TW, Nandang; Sutanto , Willi; Gianto, Gianto (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2024)
The change of payment method for electrical energy to prepaid by the Perusahaan Listrik Negara (PLN) is based on the increase in the use of electrical power, and there are areas for improvement in the postpaid system. The prepaid method uses the Standard Transfer Specification (STS) system, users enter a 20-digit token number on the kWh by pressing the kWh meter keyboard, but there are some things that could be improved if they look at the placement of the kWh meter. The user's mobility is very high. The Internet of Things (IoT) system of the kWh meter automatic button press aims to make it easier for users. The prototype uses critical components such as Raspberry PI 3B as a microprocessor, telegram as user input and output, and 12 solenoids as a keypress medium. System feasibility testing is carried out by testing the accuracy of suppression, filling time, and the receipt of messages on bot telegrams. Accuracy for each button with a test of 20 presented at a delay of 2.00 seconds to 0.04 seconds got 100% accurate results. Tested the charging time with a 100% curated delay results in the fastest time with the highest accuracy rate on a delay of 0.10 seconds to 0.04 seconds faster when compared to manual charging. On the receipt of telegram messages, get 100% test results with the consideration of 13 letters received by users. Further development can be done considering the bot display, user inputs and outputs, and customized containers on the kWh meter.